Cooperative collision avoidance algorithm for multi-vehicle based on vehicle networking technology. (5th August 2019) - Luo, Jie; Lu, Baichuan; Xu, Jin; Yang, Zhongping
This paper addresses the problem of low success rate of traditional algorithm collision avoidance and poor control of parking distance. The vehicle network system and the vehicle kinematics model are established. The paper describes accurate estimation of the vehicle driving state in tunnel intranet based on vehicle sensor and vehicle GPS data. Constraints are established for fast response disturbances, rapid stabilisation, reduced braking acceleration and deceleration, and safe distances. From the energy point of view, we consider the relative kinetic energy of any two vehicles under the vehicle network, measure the collision risk, establish the objective function, and analyse the relative kinetic energy of all vehicles approaching the preceding vehicle. In this way, a multi-vehicle cooperative collision avoidance method based on vehicle network technology is realised. The experimental results show that the algorithm has strong collision avoidance performance, and the parking distance control is better, which can ensure safety.